DESIGN AND BUILD AUTOMATIC GOODS LOCKER WITH RADIO FREQUENCY IDENTIFICATION (RFID) SECURITY - Atmiasri; Hendrikardus Gensa (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
Locker is one of the facilities that many people use to store, and locker very useful for human right now, eiter in Gym,Mall,School and other public places. In general lockers are used to store valuables so that visitors can carry out activities more freely and also to preven theft in that place. Microcontroller based Radio Frequency Identification (RFID) security locker is a locker that uses RFID security to replace the card or key that has been used in lockers that still use a manual system. Safety in the form of RFID can make it easier for locker users with a microcontroller based to control all system inputs and outputs.